2023
DOI: 10.3389/fneur.2023.1126949
|View full text |Cite
|
Sign up to set email alerts
|

Automatic risk prediction of intracranial aneurysm on CTA image with convolutional neural networks and radiomics analysis

Abstract: BackgroundIntracranial aneurysm (IA) is a nodular protrusion of the arterial wall caused by the localized abnormal enlargement of the lumen of a brain artery, which is the primary cause of subarachnoid hemorrhage. Accurate rupture risk prediction can effectively aid treatment planning, but conventional rupture risk estimation based on clinical information is subjective and time-consuming.MethodsWe propose a novel classification method based on the CTA images for differentiating aneurysms that are prone to rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…(2) Based on imaging features [ 22 24 , 4 , 9 , 25 35 ]: using deep learning techniques, such as convolutional neural networks (CNNs), to learn feature representations from intracranial aneurysm images and apply them to classification tasks. This method does not require manual feature extraction but learns feature representations from raw image data through end-to-end learning, which can better capture the complex features of intracranial aneurysms and improve classification performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Based on imaging features [ 22 24 , 4 , 9 , 25 35 ]: using deep learning techniques, such as convolutional neural networks (CNNs), to learn feature representations from intracranial aneurysm images and apply them to classification tasks. This method does not require manual feature extraction but learns feature representations from raw image data through end-to-end learning, which can better capture the complex features of intracranial aneurysms and improve classification performance.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies implemented IA recognition based on classification models [ 4 , 9 , 17 35 ], as shown in Table 1 . Combined with Tables 2 , 3 , and 4 , it can be seen that classification is currently the predominant method for IA recognition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that all three models exhibited high accuracy and were effective in discerning the status of aneurysms. Xie et al ( 36 ) combined features extracted by CNN with radiomics features and patient clinical information, employing LASSO regression to select important feature variables for constructing an SVM-based aneurysm rupture risk prediction model. The accuracy and AUC were 89.78 and 89.09%, respectively.…”
Section: Applicationsmentioning
confidence: 99%
“…Although clinical outcomes of aneurysms are influenced by various factors such as individual patient characteristics, severity of hemorrhage, different treatment modalities, and preoperative, intraoperative, and postoperative management ( 36 ), the application of radiomics and artificial intelligence in predicting the prognosis of patients with intracranial aneurysms offers new personalized treatment methods and holds great potential.…”
Section: Applicationsmentioning
confidence: 99%